2020
DOI: 10.1111/bjd.19229
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl fumarate modulates the Treg–Th17 cell axis in patients with psoriasis*

Abstract: Summary Background Dimethyl fumarate (DMF) is the active ingredient of Skilarence™ and Tecfidera™, which are used for the treatment of psoriasis and multiple sclerosis, respectively. Various immunomodulatory mechanisms of action have been identified for DMF; however, it is still unclear what effects DMF exerts in vivo in patients with psoriasis. Objectives In this study we examined the effects of DMF, both in vivo and in vitro, on T cells, which play a key role in the pathogenesis of psoriasis. Methods The fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…Meanwhile, the level of Th1-associated IFN-γ and Treg-associated TGF-β1 also showed the consistent change with Th1 and Treg cells, further confirming the pathogenic role of Th1 and Treg cells in ITP development. Interestingly, after DMF treatment, Th1 cells were significantly reduced and Treg cells were increased along with downregualted T-bet/IFN-γ and upregulated Foxp3/TGF-β1 level, consistent with previous studies showing that DMF treatment significantly decreased Th1 subset and IFN- γ secretion in patients with multiple sclerosis [ 32 ] and induced an increase in the frequency of Treg cells in patients with psoriasis [ 33 ].…”
Section: Discussionsupporting
confidence: 90%
“…Meanwhile, the level of Th1-associated IFN-γ and Treg-associated TGF-β1 also showed the consistent change with Th1 and Treg cells, further confirming the pathogenic role of Th1 and Treg cells in ITP development. Interestingly, after DMF treatment, Th1 cells were significantly reduced and Treg cells were increased along with downregualted T-bet/IFN-γ and upregulated Foxp3/TGF-β1 level, consistent with previous studies showing that DMF treatment significantly decreased Th1 subset and IFN- γ secretion in patients with multiple sclerosis [ 32 ] and induced an increase in the frequency of Treg cells in patients with psoriasis [ 33 ].…”
Section: Discussionsupporting
confidence: 90%
“…DMF treatment increased Treg frequency and decreased Th17 cells in patients with psoriasis [61]. In vitro DMF treatment induced oxidative stress, which reduced the viability and proliferation of CD4 + CD25 − conventional T cells but did not reduce Tregs [62], by virtue of the increased expression of cell surface-reduced thiols [61] or thioredoxin-1 [63], protecting Tregs from oxidative stress. The oxidative effects of DMF may favor Tregs relative to Th17 cells, which may be another mechanism for the anti-psoriatic effects of DMF.…”
Section: Dimethyl Fumarate (Dmf)mentioning
confidence: 95%
“…5 The work is relevant to our understanding of psoriasis, as the IL-17 family cytokines, in particular IL-17A, IL-17F and IL-17C, are overexpressed in psoriasis skin. 6 Blocking the IL-17 family of cytokines has a rapid clinical effect. However, it is still unknown whether blocking IL-17A alone (via ixekizumab or secukinumab), IL-17A and IL-17F (via bimekizumab), or IL-17A, IL-17C, IL-17 E and IL-17F (via brodalumab) is optimal.…”
mentioning
confidence: 99%
“…Previous studies, both in multiple sclerosis and psoriasis, have shown a beneficial effect of DMF on interleukin-17 production. 6,7 DMF can induce changes in Langerhans cell function and can reduce inflammation by inhibition of NF-jB. 8 DMF has also been shown to inhibit glyceraldehyde 3-phosphate dehydrogenase, which affects immune function via so-called immunometabolic effects.…”
mentioning
confidence: 99%